The Small Strain Stiffness Properties of Undisturbed Weathered Granite With Different Weathering Degrees - Wang, Juntao; Kong, Lingwei; Li, Chengsheng; Liu, Bingheng; Yan, JunBiao (Frontiers in Earth Science, 2022)
To evaluate the small strain stiffness properties of undisturbed weathered granite, the circular computer numerical control (CNC) abrasive wire sawing technology was applied to weathered granite sample processing and a series of resonance column tests were carried out to study the effects of weathering degree and effective consolidation pressure on dynamic shear modulus of undisturbed weathered granite. The results show that the degree of weathering and effective consolidation pressure have significant effects on the small strain stiffness properties of weathered granite. The samples with lower weathering degrees have higher dynamic shear modulus under the same effective consolidation pressure. The maximum dynamic shear modulus of samples with higher weathering degrees is more sensitive to effective consolidation pressure. Besides, a comparison between the experimental results with the previous results from other researchers indicates that the dynamic shear modulus ratio of weathered granite in the study area exceeds the parameter range obtained from others. According to the experimental results, a mathematical model of the relation between corrected standard penetration test (SPT) N’ value and dynamic shear modulus was established, and besides, the variation range of dynamic shear modulus ratio of weathered granite in the study area was given, which may provide a reference for dynamic stability analysis of engineering in the study area.